Aesthetic Theory Across the Disciplines: A Review - Lenka Lee (ESPES)
A book review of Ryynänen, Max and Zoltán Somhegyi (2023) Aesthetic Theory Across the Disciplines. 1st ed. Blue Ridge Summit: Rowman__Littlefield Publishers, Incorporated.